Customizing a Program for Older Adults Living with Frailty in Primary Care. (July 2021) - Rasiah, Jananee; O'Rourke, Tammy; Dompé, Brian; Rolfson, Darryl; Mansell, Beth; Pereira, Rachel; Chan, Titus; McDonald, Karen; Summach, Anne
Coordination of primary care is essential to improving care delivery within health systems, especially for older adults with increased health/social needs. A program jointly funded by the Canadian Foundation for Healthcare Improvement and Canadian Frailty Network, was implemented in a nurse practitioner-led clinic to address the gap in frailty care for older adults. The clinic was situated within a health and social services organization with a mandate to enhance the quality of life of older adults living in the community. Through this program, a frailty assessment pathway and social/clinical prescriptions were implemented with necessary adaptations as a result of COVID-19.